2022
DOI: 10.1101/2022.08.27.505518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LSD-induced increase of Ising temperature and algorithmic complexity of brain dynamics

Abstract: A topic of growing interest in computational neuroscience is the discovery of fundamental principles underlying global dynamics and self-organization of the brain. Statistical physics offers powerful tools to analyze complex many-body systems and has delivered computational models such as the generalized Ising model, one of the simplest known systems displaying phase transitions. Prior work has shown that different brain states may be mapped into pairwise maximum entropy Ising models at varying distances from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 107 publications
(189 reference statements)
0
3
0
Order By: Relevance
“…Notably, these systems will display enhanced sensitivity to weak perturbations, maximal information flow and long spatiotemporal scales [Ruffini & Deco, 2021], and the dynamics of the system collapse to a lower dimensional (center) manifold [Jirsa & Sheheitli, 2022]. Experimental data suggests that our brains operate close to such critical boundaries [Bak et al, 1988;Chialvo, 2004;Cocchi et al, & Friston, 2019;Ruffini et al, 2022a]. During wakeful rest, the healthy brain generates data with power-law features [He, 2014], high Shannon complexity (entropy) [Abásolo et al, 2015;Hudetz et al, 2016;Moser et al, 2019], while displaying high sensitivity to external perturbations as compared to other states such as NREM sleep [Massimini et al, 2005], under propofol anesthesia or in unresponsive awareness state [Casali et al, 2013;Casarotto et al, 2016].…”
Section: Computation As Dynamics and Criticalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these systems will display enhanced sensitivity to weak perturbations, maximal information flow and long spatiotemporal scales [Ruffini & Deco, 2021], and the dynamics of the system collapse to a lower dimensional (center) manifold [Jirsa & Sheheitli, 2022]. Experimental data suggests that our brains operate close to such critical boundaries [Bak et al, 1988;Chialvo, 2004;Cocchi et al, & Friston, 2019;Ruffini et al, 2022a]. During wakeful rest, the healthy brain generates data with power-law features [He, 2014], high Shannon complexity (entropy) [Abásolo et al, 2015;Hudetz et al, 2016;Moser et al, 2019], while displaying high sensitivity to external perturbations as compared to other states such as NREM sleep [Massimini et al, 2005], under propofol anesthesia or in unresponsive awareness state [Casali et al, 2013;Casarotto et al, 2016].…”
Section: Computation As Dynamics and Criticalitymentioning
confidence: 99%
“…The relationship between critical features of simple systems such as the Ising model and algorithmic complexity has been studied in Ruffini & Deco [2021]. In Ruffini et al [2022a], criticality aspects induced by psychedelics using the Ising model were analyzed, and it was shown that the Ising temperature is a relevant biomarker for the study of the effects of psychedelics: the resting brain, already found to be above the model's critical temperature, is further shifted into disorder under the effects of LSD. This is reflected by both an increase in Ising temperature and LZW or BDM complexity.…”
Section: Analyzing Spontaneous Brain Statementioning
confidence: 99%
“…In the Parietal cortex (PC), real-world data and model-generated data are compared, an event that results in structured consciousness [23,66]. This concept, supported by KT theory and aligned with recent research [67], underscores the significant role of the parietal cortex in distinguishing states of consciousness and involvement in the interplay among cortico-striatalthalamic structures during conscious states.…”
Section: The Modeling Enginementioning
confidence: 75%